Implementasi Program Pemberian Tablet Tambah Darah Pada Remaja Putri di SMA Negeri 5 Kota Kupang - Maria Frida Bahan; Masrida Sinaga; Tanti Rahayu; Rina Waty Sirait (Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia among adolescent girls remains a health issue with the potential to affect their future health. The distribution of iron supplements is one of the government’s strategies to prevent anemia and contribute to reducing stunting. This study aims to examine the implementation of the iron supplement program among adolescent girls at State Senior High School 5 in Kupang City using a qualitative descriptive approach. Informants were selected through purposive sampling, including public health center staff, school officials, and students, with data collection techniques involving in-depth interviews, observation, and documentation. The results indicate that the program’s objectives are well understood by public health center staff, but understanding at the school and student levels remains limited. The program has effectively reached its target audience and is supported by sufficient resources. Although communication among stakeholders has been established, activity reporting remains inconsistent, and monitoring of tablet consumption is still suboptimal. Additionally, side effects have impacted student adherence. Overall, program implementation has proceeded fairly well, but improvements are needed in education, monitoring, and reporting systems to enhance the program’s effectiveness.